Domain Ontology, an Instrument of Semantic Web Knowledge Management in e-Learning - Gladun, Anatoly Jasonovich; Rogushina, Julia Vitalijevna; Schreurs, Jeanne (International Journal of Advanced Corporate Learning (iJAC), 2012)
Domain ontology is proposed as an instrument for controlling of e-learning course results. This approach instead of traditional testing more objectively reflects the structure of studentsâ?? knowledge. Use of ontologies for knowledge representation provides interoperability of the used testing systems. The domain knowledge has been found and reuse in the semantic web world. Domain ontology developing is based on the principles of ontological analysis. The method of itâ??s use for evaluation of the learnersâ?? knowledge results is based on matching of the learnersâ?? ontology with the reference ontology proposed by the trainer/tutor. A multi-agent system for e-learning (M(e)L ) has been defined and a prototype system has been developed. In a case, the domain ontology and the semantic web representation has been applied in two e-learning university courses.